Delivering quality along with quantity: the challenge of teaching a large and heterogeneous engineering class - Chronopoulos, D. (SAGE Publications, 2018)
The challenges faced by a lecturer teaching large multidisciplinary engineering classes are identified. These are principally related to the size of the class, the extensive mathematical knowledge that is considered as prerequisite, as well as the heterogeneity of the class due to the diversity of students’ academic background and interests. In order to improve students’ engagement and retention in class, active learning techniques are employed and their impact on the performance of the class is captured through a questionnaire designed for this purpose. The statistics demonstrate that good teaching facilities and a well-prepared lecturer do not suffice for maximising students’ satisfaction, attention and retention. In order to engage the students in a large class setting, it is important to involve them in the lecture process. The employed active learning methods comprising quizzes, in class demonstration and muddiest-point cards induce a remarkably positive impact at almost no additional teaching resources.